KEPEMIMPINAN INSTRUKSIONAL KEMITRAAN KELUARGA DALAM PENGUATAN LITERASI SISWA SEKOLAH DASAR - Roid Ismail Ardho; Jaka Nugraha; Syahrul Febru Arista (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low literacy skills among elementary school students remain a critical educational challenge that cannot be resolved by schools alone. This study aims to analyze the principal's instructional leadership strategies in establishing family partnerships to strengthen students' reading and writing skills. Utilizing a qualitative approach with a case study design, data were gathered through in-depth interviews, non-participatory observations, and documentation tracking involving the principal, teachers, and parents. The data were then analyzed using the interactive model of Miles, Huberman, and Saldana. The results revealed three simultaneous managerial strategies: the formulation of a collaborative literacy covenant with the school committee, the implementation of dual-track pedagogical capacity building through teachers’ learning communities and parenting classes, and the arrangement of a routine monitoring system using daily reading logbooks. This integrated framework effectively shifted the literacy habituation from the classroom to the domestic space, achieving a 75% parental compliance rate. In conclusion, the synergy between instructional leadership and family engagement creates learning continuity that successfully mitigates students' literacy lag in elementary education.